Breve fenomenologia del lettore ai confini del nonsense (o Il lettore provocato) (ENTHYMEMA, 2012)
In this article we analyse some literary genres that have been often compared to the literary nonsense. We will particularly consider the role of the reader within these categories of texts and we will provide a sort of phenomenology of readers. Finally, we will invite to reflect upon how analysing the sphere of the reader within a literary genre can lead to relevant remarks concerning the definition of the genre itself.